Angiosarcoma secondary to postirradiation and chronic lymphedema: Case reports. Issue 48 (3rd December 2021) - Yoon, Jin A.; Shin, Myung Jun; Shin, Yong Beom; Lee, Byeong Ju; Choi, Kyung Un; Kim, Joo Hyoung
Abstract: Introduction: Angiosarcoma secondary to post-irradiation and lymphedema is rare, but it is aggressive with a poor prognosis. It is essential to understand these patients' clinical features and distinguish them from benign diseases or other malignant tumors. Patient concerns: Three patients who had radiotherapy for cancer treatment and chronic lymphedema admitted to the hospital with specific skin lesions at upper or lower extremities. Diagnosis: Excisional biopsies revealed prominent, highly atypical cells with a vasoformative area, composed of atypical, large epithelioid cells with vesicular nuclei, prominent nucleoli, and mitoses. Immunohistochemistry revealed diffuse expression of endothelial cell markers suggestive of angiosarcoma. Interventions: One patient had shoulder disarticulation with wide excision with adjuvant radiotherapy and chemotherapy and other 2 discontinued the treatment. Outcomes: After the treatment, one patient was transferred to rehabilitation department for shoulder disarticulation prosthesis fitting without recurrence sign for 1 year. Two patient refused further treatment and was lost to follow-up. Conclusion: In cases of patients with irratiation and chronic lymphedema, clinical findings suggestive of angiosarcoma, biopsy and imaging studies should be performed as soon as possible.